Community forestry and rural livelihoods : a case study of the contribution of natural resources to livelihoods of rural communities in the Northern Province, South Africa - Masutha, Takalani (Takalani Henry) (Stellenbosch : Stellenbosch University, 2012)
Thesis (MScFor)--Stellenbosch University, 2002.